Polymorphisms in CYP1A2, CYP2C9 and ABCB1 affect agomelatine pharmacokinetics - Saiz-Rodríguez, Miriam; Ochoa, Dolores; Belmonte, Carmen; Román, Manuel; Vieira de Lara, Danilo; Zubiaur, Pablo; Koller, Dora; Mejía, Gina; Abad-Santos, Francisco (Journal of psychopharmacology (Oxford), 2019)
Agomelatine is an agonist of the melatoninergic receptors used for the treatment of depression. Our aim was to evaluate the effect of genetic polymorphisms in metabolising enzymes and the P-glycoprotein transporter on agomelatine pharmacokinetics and pharmacodynamics. Twenty-eight healthy volunteers receiving a single 25 mg oral dose of agomelatine, were genotyped for nine polymorphisms in cytochrome P450 enzymes ( CYP1A2, CYP2C9 and CYP2C19) and adenosine triphosphate-binding cassette subfamily B member 1 ( ABCB1), by real-time polymerase chain reaction . Agomelatine concentrations were measured by high performance liquid chromatography coupled to a tandem mass spectrometry detector. We calculated a CYP1A2 activity score that was directly correlated with agomelatine pharmacokinetics. Individuals with a decreased enzyme activity (*1C carriers) had a lower clearance and accumulated higher concentrations of agomelatine. In contrast, individuals with a high CYP1A2 inducibility (*1F or *1B carriers) showed an extensive clearance and lower agomelatine concentrations. The apparently marked differences between races were due to the different CYP1A2 genotype distribution. CYP2C9 intermediate/poor metabolisers showed a higher area under the concentration-time curve and maximum concentration. ABCB1 G2677T/A polymorphism affected the time to reach maximum concentration, as subjects carrying A/A+A/T genotypes showed higher values. No association was found for CYP2C19 phenotype. Agomelatine did not produce any change in blood pressure, heart rate or QT interval. CYP1A2 polymorphisms affect agomelatine pharmacokinetics. CYP1A2 phenotype inferred from the genotyping of CYP1A2*1C, *1F and *1B alleles might be a potential predictor of agomelatine exposure. ABCB1 G2677T/A could affect agomelatine absorption, as subjects with A/A+A/T genotypes had lower agomelatine concentration and they take more time to reach the maximum concentration.